2017
DOI: 10.1016/j.ygyno.2017.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility, safety and clinical outcomes of cardiophrenic lymph node resection in advanced ovarian cancer

Abstract: Objectives: Surgical resection of enlarged cardiophrenic lymph nodes (CPLNs) in primary treatment of advanced ovarian cancer has not been widely studied. We report on a cohort of patients undergoing CPLN resection during primary cytoreductive surgery (CRS), examining its feasibility, safety, and potential impact on clinical outcomes. Methods: We identified all patients undergoing primary CRS/CPLN resection for Stages IIIB-IV high-grade epithelial ovarian cancer at our institution from 1/2001–12/2013. Clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 33 publications
0
45
0
Order By: Relevance
“…In 2006, our goal for PDS evolved from residual disease ≤10 mm to either CGR or as minimal residual tumor as possible [7]. During 2010 to 2013, 3 additional changes were gradually adopted: routine performance of cardiophrenic lymph node resection [20], use of the selection criteria for NACT as described by Aletti et al [21], and implementation of earlier operative start times [18]. The decision to define 2010 as the division point between Groups 2 and 3 was also influenced by the increase in our NACT rates after 2010 [22].…”
Section: Methodsmentioning
confidence: 99%
“…In 2006, our goal for PDS evolved from residual disease ≤10 mm to either CGR or as minimal residual tumor as possible [7]. During 2010 to 2013, 3 additional changes were gradually adopted: routine performance of cardiophrenic lymph node resection [20], use of the selection criteria for NACT as described by Aletti et al [21], and implementation of earlier operative start times [18]. The decision to define 2010 as the division point between Groups 2 and 3 was also influenced by the increase in our NACT rates after 2010 [22].…”
Section: Methodsmentioning
confidence: 99%
“…Treatment of patients with CPLN involvement includes optimal debulking and complete gross resection options. Optimal debulking surgery is associated with a 68.9 months median overall survival (OS) while patients who obtained a complete gross resection (CGR) had a median OS of 72.3 months [39].…”
Section: Pathways and Metastatic Sites Of Ovarian And Peritoneal Cmentioning
confidence: 99%
“…Furthermore, cardio phrenic lymph nodes (CPLN) are located above the abdominal cavity and diaphragm and are, by convention, considered radiologically positive if the short axis in the transaxial plane is ≥5 mm. However, how they should be handled in surgical care and their role in ovarian cancer prognosis have been debated [10,11]. Interestingly, a recent paper (predominantly high grade serous OC) [10] indicated that there was a stronger correlation between CPLN positivity and peritoneal carcinomatosis of the upper abdomen (especially of the diaphragm) than between CPLN positivity and abdominal lymph node status, which makes the two parameters (CT-PCI and CPLN) particularly interesting to study together.…”
Section: Introductionmentioning
confidence: 99%